Fluoride-assisted synthesis of 1,4,5,6-tetrahydropyridazines via [4+2] cyclodimerization of in situ-generated azoalkenes followed by a C-N bond cleavage - Shelke, Anil M.; Suryavanshi, Gurunath (Organic Letters, 2016)
An unexpected CsF-assisted C-N bond cleavage was exploited to synthesize highly functionalized and biologically important 1,4,5,6-tetralrydropyridazine derivatives from alpha-halo N-acylhydrazohes in excellent yields. The extrusion of nitrogen and the [4 + 2] cycloaddition between in situ-generated azoalkenes is a key reaction in the process. The identified methodology is suitable for synthesizing a wide variety of analogues of tetrahydropyridazines, which are prevalent in many medicinally important small molecules. The reaction conditions are mild, high-yielding, and amenable for the gram scale.